Caracterización del estado de conservación de las especies presentes en los principales humedales altoandinos de la concesión para Conservación Alto Huayabamba (CCAH) - García Díaz, Javier Ernesto (2012)
The high Andean wetlands play a dominating role in the ecosystems balance in general because it houses plant and animal life unique in its kind, its study is essential to understand the dynamics of all hydrological processes in the Andean has in. In this regard, this research work seeks to estímate the condition of conservation of the species of three taxonomic groups, which are plants (herbs), birds and amphibians, in order to achieve this work in the frrst place was sampled in the wetlands in four representative sectors of the High Huayabamba Conservation Concession that are: Huayabamba, Yonán, Quinguyacu and Yámpio; later ofhaving identified the species, it is proceeded to evaluate all the raised parameters that will • serve to determine the degree ofthreat that characterizes him. For the evaluation of these species one used different methodologies, for plants sample transects with repetitions every 100 meters, for birds Abundance Indexes Kilometric (IKA) and Abundance Punctual Index (IP A), for the amphibians evaluation directed capture method, Under this context, the work shows as a result the floristic composition and relative frequency of 65 herbaceous species, frequency and abundance of 23 birds species and 3 amphibians species, to subsequently determine that there is 1 vulnerable herbaceous species and 7 species of endangered birds. Key words: High Andean wetlands, floristic composition.